Design of Interactive Media for Japanese M-Learning Based on Android Using UML and Waterfall Model - Apriade Voutama; Elfina Novalia (Information System; Universitas Buana Perjuangan Karawang, 2025)
The development of open source technology has created many innovations created by developers in creating Android-based applications. One of them is creating interactive media M-Learning Japanese language learning based on Android. Japanese M-Learning is made to facilitate students in the learning process and provide interactive convenience in improving Japanese language skills. M-Learning is made using the Android programming language with UML (Unified Modeling Language) design analysis tools and the waterfall model. The initial analysis uses the Usecase model to determine the actors involved in the system, and the flow of actor activities using the Activity and Sequence models and several other supporting models. The User Interface is made to describe the system being built and the Flowchart is designed to see the scheme running on the Japanese M-Learning interactive media system. The results of the analysis were carried out by taking satisfaction data from 30 student respondents, 81% stated that this Interactive Media was Good.